The Impact of Quality Exercises in the Development of Compatibility and Motor Elasticity and Learning the Skill of Preparing for Students in Volleyball - Firas Kahsop Rashid (Journal of Global Pharma Technology, 2018)
The importance of research lies in the set of quality exercises, their knowledge of compatibility, motor elasticity, and learning the skill of preparing volleyball for students.The problem of research: it was centered on the fact that most students are slow to learn motor skills, especially in the skill of set, because they are skills that require dynamic compatibility and high flexibility and lead in multiple forms while, and they need a great deal of time to learn and master this skill correctly in terms of ringing, cruise and proper timing, researchers believe that the reason for this is that teachers are less likely to use a variety of exercises and limit them to a specific type of exercise, which makes learning the skill of the set need a great deal of time.The Objective of ResearchPrepare quality exercises in the development of compatibility and motor elasticity and learn the skills of volleyball set for students.Identification of the impact of specific exercises in the development of compatibility and mobility flexibility for students.Identify the impact of specific exercises in learning the skills of volleyball set for students.Research HypothesisThere is an impact of quality exercise in the development of compatibility and mobility flexibility for students.There is an impact of specific exercise in learning the skills of volleyball set for students.As for research methodology and field procedures, researchers used the experimental approach to solve the research problem, and the research community was identified by the second-stage students of the Faculty of Physical Education and Sports Sciences/University of Kufa, and distributed to two groups (experimental and female officers) in the simple random manner ( The draw).The most important conclusions and recommendations are as follows:Specific exercises have helped to develop the kinetic compatibility of the men and the arms of the experimental group.Specific exercises have helped to develop mobility flexibility.Specific exercises have helped to learn the technical performance of the volleyball set skill of the pilot group.Keywords: Quality exercises, Motor elasticity and learning.